Airport Security: Examining The Current State Of Acceptance Of Biometrics And The Propensity Of Adopting Biometric Technology Fo - Sumner, Kristine (2007)
The terrorist attacks of September 11, 2001 propelled the issue of aviation security to the forefront of the U.S. domestic agenda. Although hundreds of individual airports exist in the U.S., the travel activities at each of these airports combine to holistically comprise an aviation system that represents a significant portion of the U.S. social and economic infrastructure. Disruption at one airport resulting from a criminal act, such as terrorism, could exert detrimental effects upon the aviation system and U.S national security (9/11 Commission, 2004). Each U.S. airport is individually responsible for various aspects of security including the control of physical access to sensitive and secure areas and facilities (9/11 Commission, 2004). Biometric technology has been examined as one method of enhancing airport access control to mitigate the possibility of criminal acts against airports. However, successful implementation of biometric technology depends largely on how individual security directors at each airport perceive, understand, and accept that technology. Backgrounds, attitudes, and personal characteristics influence individual decisions about technology implementation (Rogers, 1995; Tornatzky and Fleischer, 1990). This study examines the problem of airport access control, as well as, the current trends in biometric technology. Utilizing a survey of airport security directors and security managers, this study draws upon innovation diffusion theory and organizational theories to determine what personal, organizational, and technical variables contribute to the propensity of airport security directors and managers to adopt biometric technology for airport access control